Digital Affordances on Speaking English Fluently: Learning English as a Second Language - Musthafa Fadli Perkasyah; Christiana Suriani Debataraja; Sholihatul Hamidah Daulay (Journal on Education, 2023)
Speaking is a skill that involves verbal communication, such as deriving meaning between two or more people as a speaker and listener. The pread of technology make people easier to study. On of the digital tool to improve speaking ability is by using digital story telling or called DST. Lots of researcs about DST have been published and told how effective it is. The effectiveness of DST as a tool to support the learning of all four English language skills. In this study, a descriptive research technique, case studies, was used. The case study aims to explore that examine the characteristics of existing cases and try to describe them in detail. In this study used digital media in teaching speaking. The two most important methods used by Toontastic turned out to be scaffolding and subject familiarity. In their learning Regarding protocol, more than 50% of students said the gradual development of the story was driven by: Toontastic makes it easy to create your own stories. From a social constructivist perspective, Toontastic's resources were the bridge that took ZPD's performance to the next level.